Model Digitalisasi Manajemen Risiko dalam Pembiayaan Ijarah di Bank Syariah Indonesia - M. Masrukhan; Setya Pramono (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine and design a digital risk management model in ijarah financing at Bank Syariah Indonesia (BSI). The research is driven by the urgency of digital transformation in the Islamic banking sector while maintaining compliance with Sharia principles, particularly in risk management. The ijarah contract carries unique risk characteristics such as asset risk, moral hazard, and default risk, which must be systematically managed. This research adopts an exploratory qualitative approach through a case study at BSI, using semi-structured interviews and documentation as data collection methods. The findings indicate that the application of digital systems such as risk dashboards, credit scoring automation, and digital traceability significantly enhances risk mitigation in ijarah financing. The study proposes a Sharia-compliant digital risk management model that can be implemented adaptively and efficiently in BSI and other Islamic banks. The model not only strengthens risk control but also improves operational efficiency and transparency. This research contributes both practically and theoretically to the development of Sharia-based digital risk management practices.